N160 of Aiolos Determines its DNA‐Binding Activity. Issue 11 (11th July 2019) - Wang, Hao; Xu, Zhao; Du, Wei; Lin, Zhenzhen; Liu, Zhe
ABSTRACT: Aiolos is a transcription factor of the Ikaros family. It is expressed in lymphocytes and plays a vital role in the development of lymphatic system. Recently, Aiolos has been found to be ectopically expressed in lung cancer cells and promotes cancer metastasis through repression of p66 Shc expression. Blocking DNA‐binding activity of Aiolos may benefit cancer patients by preventing further metastasis. However, it is not clear which sequence is essential for its DNA binding. In this study, we found that N160 is a key amino acid to determine the DNA‐binding activity of Aiolos. Mutation of N160A resulted in loss of peripheral heterochromatin localization and dissociation with its target gene. Accordingly, Aiolos with N160A could not change the expression of its target genes. Thus, we identified the amino acid (N160) that is essential for Aiolos binding to DNA. Anat Rec, 302:2014–2019, 2019. © 2019 American Association for Anatomy